Kontribusi Bahasa Arab Dalam Proses Kemajuan Ilmu Pengetahuan Pada Abad XIII-XVIII Masehi - Hamid, Mas'an (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2025)
This research examines the contribution of Arabic to the advancement of science in the XIII-XVIII centuries AD. This era was marked by the spread of Islam, which influenced civilization, including the mastery and development of science. However, research on the specific role of Arabic in knowledge transfer and innovation is still limited. Using a descriptive qualitative approach based on philology, this study analyzes primary sources such as The Holy Quran and hadith and scientific works in Arabic, such as Ahmad Syafiq Al-Khatib’s A new Dictionary of Scientific and Technical Terms. Results show that Arabic served as an important medium in translating, developing and disseminating knowledge in various fields, including medicine, philosophy, mathematics and geography. Arabic supported the interaction between civilizations and drove Europe’s intellectual transformation during the Renaissance. Therefore, Arabic facilitated the transfer of knowledge and enriched global civilization with its intellectual contributions.